Bicycle helmet with a pulse sensor, temperature and LED signal / Muhammad Haziq Ismail - Ismail, Muhammad Haziq (2003)
Since cycling is a common form of entertainment and transportation, safety precautions need to be given more attention. While conventional bicycle helmets provide impact protection, the addition of an LED signaling system, temperature monitoring system, and pulse sensor is intended to improve safety. The project aims to deliver a complete system that improves road visibility, offers real-time health analytics, and protects riders. The idea was inspired by the growing convergence of technology and safety, which highlights the need to go beyond the features found in traditional helmets. By including a pulse sensor, the cyclist's heart rate can be continuously monitored, protecting their cardiovascular system and avoiding overexertion. Temperature monitoring enhances rider safety and comfort in a variety of weather scenarios. By improving visibility, LED signaling systems lower the chance of accidents. Iterative improvements, testing, assembly, and careful component procurement are all part of the technique. Why this idea was inspired because the inclusion of temperature monitoring in the smart helmet was conceived with the aim of enhancing rider safety and comfort across diverse weather conditions. This feature equips cyclists with real-time insights into their surroundings, enabling them to adapt their rides based on ambient temperatures. It addresses a critical aspect of the cycling experience, ensuring that riders are better prepared and more comfortable, regardless of environmental variations. Furthermore, the integration of LED signaling systems was inspired by a commitment to improving visibility and communication on the road. Recognizing the vulnerability of cyclists, especially in busy or low-light conditions, the LED signals serve as an innovative safety feature. This not only reduces the likelihood of accidents but also establishes a proactive means for cyclists to communicate their intentions to other road users.